2002
DOI: 10.1074/jbc.m200822200
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorylation of Threonine 68 Promotes Oligomerization and Autophosphorylation of the Chk2 Protein Kinase via the Forkhead-associated Domain

Abstract: Phosphorylation of Thr-68 by the ataxia telangiectasia-mutated is necessary for efficient activation of Chk2 when cells are exposed to ionizing radiation. By an unknown mechanism, this initial event promotes additional autophosphorylation events including modifications of Thr-383 and Thr-387, two amino acid residues located within the activation loop segment within the Chk2 catalytic domain. Chk2 and related kinases possess one or more Forkhead-associated (FHA) domains that are phosphopeptide-binding modules b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
205
0
1

Year Published

2004
2004
2016
2016

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 174 publications
(213 citation statements)
references
References 27 publications
7
205
0
1
Order By: Relevance
“…The variant protein is clearly overexpressed, but is phosphorylated on Thr68 at markedly reduced levels compared to that of wild-type, endogenous CHK2. Dimerisation is proposed to represent an important step in the regulation of CHK2 activity (Ahn et al, 2002;Xu et al, 2002). However, we were not able to detect dimerisation of variant protein with the wild-type CHK2 in cells that ectopically expressed both proteins (data not shown), indicating that the truncated protein is not likely to affect wild-type CHK2 activity in this way, even if it is expressed at very low levels (undetectable with our methodology).…”
Section: Overexpression Of the 1100delc Mutant Does Not Affect Endogementioning
confidence: 63%
See 1 more Smart Citation
“…The variant protein is clearly overexpressed, but is phosphorylated on Thr68 at markedly reduced levels compared to that of wild-type, endogenous CHK2. Dimerisation is proposed to represent an important step in the regulation of CHK2 activity (Ahn et al, 2002;Xu et al, 2002). However, we were not able to detect dimerisation of variant protein with the wild-type CHK2 in cells that ectopically expressed both proteins (data not shown), indicating that the truncated protein is not likely to affect wild-type CHK2 activity in this way, even if it is expressed at very low levels (undetectable with our methodology).…”
Section: Overexpression Of the 1100delc Mutant Does Not Affect Endogementioning
confidence: 63%
“…In response to ionising radiation (IR), threonine 68 of CHK2 is rapidly phosphorylated by ataxia telangiectasia mutated (ATM) (Matsuoka et al, 2000;Zhou et al, 2000), allowing oligomerisation and transautophosphorylation of CHK2 (Ahn et al, 2002;Xu et al, 2002). Activated CHK2 is involved in maintaining the G1/S and G2/M checkpoints by phosphorylation of CDC25A, CDC25C and p53 (Chaturvedi et al, 1999;Shieh et al, 2000;Falck et al, 2001), and repair of double-strand DNA breaks via homologous recombination (HR) through phosphorylation of BRCA1 (Lee et al, 2000).…”
mentioning
confidence: 99%
“…It had been shown previously that phosphorylation of Chk2 on Thr68 is required for full activation of Chk2 via auto-(trans-or cis)phosphorylation. [9][10][11][12][13][31][32][33][34] We therefore investigated the role of Thr68-phosphorylation in the electrophoretic mobility shift of Chk2. We found that a Chk2 mutant, the alanine68 mutant (HA-Chk2 (T68A)), did not undergo the mobility shift when overexpressed (data not shown), indicating that Thr68 is required.…”
Section: Effect Of Wip1 On Thr68 Phosphorylation Of Chk2 Induced By Dmentioning
confidence: 99%
“…These results are consistent with the idea that Wip1 can dephosphorylate the phosphorylated-Thr68 in Chk2 induced by g-irradiation or ectopic overexpression of Chk2, and that Thr68-phosphorylation of Chk2 is a prerequisite event for (trans-)phosphorylating Thr387 (and possibly Thr383) in Chk2 (see Figure 2c). [31][32][33][34] We also examined whether Wip1 could dephosphorylate Ser19, Ser33/35, Thr432, and Ser516 in Chk2. As shown in Figure 3a, GST-Wip1 (WT), but not GST-Wip1 (D314A), dephosphorylated-Ser19, -Ser33/35, -Thr432, but not Ser516 in Chk2 in vitro.…”
Section: Effect Of Wip1 On Thr68 Phosphorylation Of Chk2 Induced By Dmentioning
confidence: 99%
“…We illustrated the scope of the technique by the preparation of phosphorylated CHK2 protein. CHK2 is a serine/threonine kinase which upon activation by phosphorylation on Thr‐68 plays a central role in DNA damage response 27. Furthermore, it is involved in cell cycle checkpoint activation, apoptosis, viral infectivity and other pathways 28.…”
mentioning
confidence: 99%